Reciprocal regulation of actin filaments and cellular metabolism - Geyao Liu; Jiayi Li; Congying Wu (European Journal of Cell Biology, 2022)
For cells to adhere, migrate and proliferate, remodeling of the actin cytoskeleton is required. This process consumes a large amount of ATP while having an intimate connection with cellular metabolism. Signaling pathways that regulate energy homeostasis can also affect actin dynamics, whereas a variety of actin binding proteins directly or indirectly interact with the anabolic and catabolic regulators in cells. Here, we discuss the inter-regulation between actin filaments and cellular metabolism, reviewing recent discoveries on key metabolic enzymes that respond to actin remodeling as well as historical findings on metabolic stress-induced cytoskeletal reorganization. We also address emerging techniques that would benefit the study of cytoskeletal dynamics and cellular metabolism in high spatial-temporal resolution.